An acute gastroenteritis outbreak associated with person-to-person transmission in a primary school in Shanghai: first report of a GI.5 norovirus outbreak in China - Li, Jian (BMC Infect Dis, 2018)
BACKGROUND: GII noroviruses are a common cause of acute gastroenteritis (AGE) outbreaks in institutional settings globally. However, AGE outbreaks caused by GI norovirus, especially the GI.5 genotype, are relatively uncommon. METHODS: In February 2017, an AGE outbreak occurred in a primary school in Shanghai, China. An outbreak investigation was undertaken, and fecal specimens, rectal swabs, and environmental swabs were collected. Pathogen detection was performed and the positive specimens were characterized by gene sequencing. RESULTS: The descriptive epidemiological analysis suggested that this outbreak, involving 19 cases in two classes (designated classes A and B), was a small-scale propagated epidemic and person-to-person transmission was the most plausible transmission mode. The outbreak comprised two peaks, with 15 cases occurring in class A during the main peak and four cases occurring in class B in the subsequent minor peak. The primary attack rate was 38% and the secondary attack rate was 10%. Univariable logistic regression indicated that contacting a suspect case was a risk factor for norovirus infection, with an unadjusted OR of 5.6 (95% CI: 1.6–20.1). Six fecal specimens were positive for GI norovirus, with a single genotype, GI.5 norovirus, being involved, as characterized by genotyping. This outbreak was the first reported outbreak of GI.5 norovirus in China. CONCLUSIONS: This study implies that GI.5 norovirus is a potential agent of outbreaks spread by person-to-person transmission in institutional settings. The investigation highlights the importance of sensitive surveillance, timely isolation of individuals who are ill, adequate hand hygiene, and proper environmental disinfection for prevention and control of AGE outbreaks caused by norovirus.